(untitled) - Barbas, Carlos F (Cold Spring Harbor, NY, 2001)
Includes bibliographical references and index
Keywords: Affinity chromatography -- Laboratory manuals; Bacteriophages -- Laboratory manuals; Microbial biotechnology -- Laboratory manuals; Peptides -- Biotechnology -- Laboratory manuals; Proteins -- Biotechnology -- Laboratory manuals; Sắc ký ái lực -- Hướng dẫn phòng thí nghiệm; Thực khuẩn thể ; Công nghệ sinh học vi sinh vật; Chất peptides -- Công nghệ sinh học